Virtue Jurisprudence
VII, 268 p.
Keywords: This book is the first authoritative text on virtue jurisprudence - the belief that the final end of law is not to maximize preference satisfaction or protect certain rights and privileges, but to promote human flourishing. Scholars of law, philosophy and politics illustrate here the value of the virtue ethics tradition to modern legal theory.